Pengaruh Kualitas Pelayanan, Keterjangkauan Harga dan Promosi Terhadap Kepuasan Pelajar Pengguna GoCar Hemat Cianjur - Neng Mutiara Salsabila Bila; Mochamad Afrizal Maulana (Forum Kerjasama Pendidikan Tinggi, 2026)
The development of application-based transportation services has influenced consumer behavior, including students who are a potential user segment. However, differences in service quality, price affordability and promotional strategies for GoCar Hemat services often give rise to complaints that have the potential to reduce user satisfaction. This study aims to analyze the influence of service quality, price and promotion on the satisfaction of GoCar Hemat users among high school students in Cianjur District. The study uses a quantitative approach with a survey method through a questionnaire of 100 respondents selected using purposive sampling based on specific criteria and analyzed using multiple linear regression with the help of SPSS version 31. The results show that service quality, price affordability and promotion have a positive and significant effect on consumer satisfaction, with price affordability being the dominant factor. The three variables simultaneously contribute 79.9% to consumer satisfaction, while 20.1% is influenced by other factors outside the model. These findings emphasize the importance of improving service quality, affordable pricing strategies and targeted promotions in enhancing customer satisfaction, particularly among the student segment in non-metropolitan areas. This study is expected to provide practical contributions to Gojek's management and academic references for the development of online transportation service marketing studies